Pacific alliance allies and its commercial opportunities with Colombia (2018)
According to the Americas Society / Council of the Americas, the members of the P.A. account around 37% of Latin America’s total GDP, 50% of the country’s exports and 45% of foreign investment. ( Americas Society / Council of the Americas, 2018). Due to de dynamism of this alliance the world has started to interest in it. Now, the P.A. has about 52 observer countries who can participate of the meetings of the Alliance and can also apply to become a full member of the P.A. if they have trade deals in place with at least half of the coalition’s full members. They are, in America: Argentina, Canada, Costa Rica, Ecuador, El Salvador, United States, Guatemala, Haiti, Honduras, Panama, Paraguay, Dominican Republic, Trinidad and Tobago, and Uruguay. In Africa: Egypt and Morocco. In Asia: China, Korea, India, Indonesia, Israel, Japan, Singapore, and Thailand. In Europe: Germany, Austria, Belgium, Croatia, Denmark, Slovakia, Slovenia, Spain, Finland, France, Georgia, Greece, Hungary, Italy, Lithuania, Norway, Netherlands, Poland, Portugal, United Kingdom, Czech Republic, Romania, Sweden, Switzerland, Turkey, and Ukraine. And last in Oceania: Australia and New Zeeland. Now, there are already two countries in the process to access as full member to the P.A., Costa Rica and Panama. (International Centre for Trade and Sustainable Development, 2018)